SWOT ANALYSIS OF ECOTOURISM DESTINATION OF OESINA BEACH: CHALLENGES, OPPORTUNITIES, DEVELOPMENT STRATEGIES - Soimin, Muhamad (Jurnal Silva Samalas, 2023)
The abstract Natural heritages and cultural values possessed by the East Nusa Tenggara region have the potential to be developed towards the tourism industry based on sustainable tourism principles in the form of ecotourism. A potential ecotourism destination that occurs in the region is Oesina Beach, the 1 km white sandy beach with a huge marine potential. This ecotourism destination is situated in Lifuleo village. This research is an investigative-descriptive study with an approach of SWOT Analysis (Strength, Weakness, Opportunity, and Threat) combined with IFES (Internal Factor Analysis Strategy) and EFES (External Factor Analysis Strategy). The SWOT analysis reveals: 1) several strengths and opportunities that can be optimized; 2) several weaknesses and threats that can be mitigated by optimization strategies; and 3) several proposed optimization strategies based on S-O (strength to optimize opportunity), W-O (opportunity to minimize weakness), T-S (strength to mitigate threat), and T-W (effort to address threat and weakness). IFES and EFES analysis indicate that the Oesina ecotourism destination is located in Quadrant I, meaning that the ecotourism destination requires promotion through market development penetration, market penetration, and product development. Following this, all related stakeholders of governments, management, and local-dependent communities; need to build a strong collaboration towards a successful implementation of optimization strategies. The result of this study is expected to be used as a reference for related stakeholders to design and implement a robust strategy to develop the ecotourism destination in the form of a scientific-based policy. This, therefore, will promote more benefits as conservation tools as well as enable the dependent community to gain more socioeconomic advantages.